Conservation Agriculture and Scale of Appropriate Agricultural Mechanization in Smallholder Systems - Singh, Yadvinder; Sidhu, Harminder S.; Jat, Hanuman Sahay; Singh, Manpreet; Chhokar, RS; Setia, Raj; Jat, Mangi Lal (2020)
This manual has focused on the need to amplify and accelerate adoption of conservation agriculture (CA) practices that enable productivity increases on a sustainable basis. The development of the training manual on ‘Conservation Agriculture and Scale Appropriate Agricultural Mechanization in Smallholder Systems’ is an outcome of the series of advanced training programs on Conservation Agriculture over past one decade. The objectives of this training manual are; (1) To foster capacity building of researchers, extension workers, farmers and machinery manufacturers to promote CA in Asia and Africa; and (2) To raise the awareness of policy planners and decision makers to develop a strategic plan for the development of CA and agricultural mechanization in the developing world. There are several initiatives in South Asia and Africa to promote CA practices as environment-friendly and alternative to conventional agriculture. However, little has been done to document the CA practices or even lessons learnt from these initiatives. Farmers today still lack access to information on CA practices. This is a comprehensive manual that explains in a step by step easy to follow manner on how to implement CA by smallholders in Asia and Africa. It explains what CA is, and why it is important, how to use CA principles in the field and highlights the issues and challenges that researchers, farmers, machinery manufacturers and service providers may encounter when they adopt and adapt CA practices. This manual aims to be a valuable reference and is intended for use by researchers, agricultural extension officers/workers, farmers, machinery manufacturers and service providers to promote CA in Asia and Africa for increasing productivity and reducing poverty. It is written in clear, easy-to-understand language, and is illustrated with numerous figures and tables. It is not intended to cover the subject of conservation agriculture comprehensively but to provide an overview of the principles and practices. Indeed, as the training draws from many distinct disciplines, it is unlikely that any one person will have the necessary technical skills to cover the complete course content. Manual also focuses on two crucial aspects: the provision of farm mechanization services as a viable business opportunity for entrepreneurs, and the essential criteria of raising productivity in an environmentally sensitive and responsible way. This manual is also designed to serve as source of information for custom hire service providers – whether already in the business or intending to start their own hire service business – with skills and competencies in both the technical and the management aspects of the small-scale mechanization business. CA to reach smallholder farmers needed the publication of simplified technical manual. This manual contains useful technical information on CA practices that offer practical answers to questions normally asked by farmers of what, why, how.